1998
DOI: 10.1016/s0140-6736(97)07382-0
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term postoperative cognitive dysfunction in the elderly: ISPOCD1 study

Abstract: Our findings have implications for studies of the causes of cognitive decline and, in clinical practice, for the information given to patients before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
1,112
10
49

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,094 publications
(1,210 citation statements)
references
References 27 publications
39
1,112
10
49
Order By: Relevance
“…2 In non-cardiac surgery, an international trial of elderly patients (median age 68, range 60-81 yr) demonstrated a 26% incidence of POCD one week after surgery, with 10% having persistent POCD three months later. 3 Younger patients (median age 51, range 40-60 yr) had a lesser incidence of POCD at one week postoperatively (19%), and this decreased to 6% after three months, similar to that of control subjects. 4 These studies were unable to distinguish between the contribution of major surgery and anesthesia to the observed incidence of POCD.…”
Section: Conclusion : Le Premier Jour Après Une Opération Mineure L'mentioning
confidence: 54%
See 1 more Smart Citation
“…2 In non-cardiac surgery, an international trial of elderly patients (median age 68, range 60-81 yr) demonstrated a 26% incidence of POCD one week after surgery, with 10% having persistent POCD three months later. 3 Younger patients (median age 51, range 40-60 yr) had a lesser incidence of POCD at one week postoperatively (19%), and this decreased to 6% after three months, similar to that of control subjects. 4 These studies were unable to distinguish between the contribution of major surgery and anesthesia to the observed incidence of POCD.…”
Section: Conclusion : Le Premier Jour Après Une Opération Mineure L'mentioning
confidence: 54%
“…Risk factors for POCD identified by these studies included advancing age, duration of anesthesia, and repeat surgery. [1][2][3][4] Serum markers of neuronal injury, S-100ß protein and Neuron-Specific Enolase (NSE) have been evaluated after different kinds of surgery, with conflicting results. [5][6][7][8] Levels are elevated after cardiac surgery and S-100ß protein in particular may be correlated to POCD after some types of non-cardiac surgery.…”
Section: Conclusion : Le Premier Jour Après Une Opération Mineure L'mentioning
confidence: 99%
“…The international study on post‐operative cognitive dysfunction (ISPOCD 1) study published in the lancet in 1998 demonstrated long‐term POCD in elderly patients undergoing non‐cardiac surgery 90. However, the second study published in 2003 (ISPOD2) found no significant difference in the incidence of cognitive dysfunction 3 months after either general or regional anaesthesia 91.…”
Section: Surgery and Cognitive Dysfunctionmentioning
confidence: 99%
“…Rudolph and Marcantonio reported that the rate of postoperative delirium ranges from 5 % to approximately 50 %, depending on the type of surgery [8]. Moller et al reported that approximately 25 % of elderly patients exhibit cognitive deterioration for one week after non-cardiac procedures and 10 % exhibit dysfunction for 3 months after major surgery under general anesthesia [9]. However, several months after surgery, the incidence decreases to less than half of the patients, and at one year after surgery, decreases to approximately one-quarter of patients.…”
Section: Current Understanding Of Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…Most previous studies that utilized the neurological assessments used in cardiac surgery studies failed to detect any cognitive dysfunction after non-cardiac surgery. More recent studies have identified other factors associated with cognitive dysfunction, i.e., age, preoperative level of education and postoperative complications are listed as risk factors, while the effect of type of anesthesia may be minor [9,15].…”
Section: Risk Factors and Proposed Mechanisms Of Cognitive Dysfunctionmentioning
confidence: 99%